Basin scale controls on CO2 and CH4 emissions from the Upper Mississippi River. Issue 5 (2nd March 2016) - Crawford, John T.; Loken, Luke C.; Stanley, Emily H.; Stets, Edward G.; Dornblaser, Mark M.; Striegl, Robert G.
Abstract: The Upper Mississippi River, engineered for river navigation in the 1930s, includes a series of low‐head dams and navigation pools receiving elevated sediment and nutrient loads from the mostly agricultural basin. Using high‐resolution, spatially resolved water quality sensor measurements along 1385 river kilometers, we show that primary productivity and organic matter accumulation affect river carbon dioxide and methane emissions to the atmosphere. Phytoplankton drive CO2 to near or below atmospheric equilibrium during the growing season, while anaerobic carbon oxidation supports a large proportion of the CO2 and CH4 production. Reductions of suspended sediment load, absent of dramatic reductions in nutrients, will likely further reduce net CO2 emissions from the river. Large river pools, like Lake Pepin, which removes the majority of upstream sediments, and large agricultural tributaries downstream that deliver significant quantities of sediments and nutrients, are likely to persist as major geographical drivers of greenhouse gas emissions. Key Points: Upper Mississippi River is a recurrent CO2 sink Upper Mississippi River is a consistent CH4 source River biology, physics, and sediments control gas emissions